2010
DOI: 10.1080/10615800902818771
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptoms and dominant emotional response to a traumatic event: an examination ofDSM-IVCriterion A2

Abstract: To qualify for a diagnosis of posttraumatic stress disorder (PTSD), the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) requires that individuals report experiencing dominant emotions of fear, helplessness, and horror during the trauma (Criterion A2). Despite this stipulation, traumatic events can elicit a myriad of emotions other than fear, such as anger, guilt or shame, sadness, and numbing. The present study examined which emotional reactions to a stressful event in a college … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 13 publications
5
61
0
1
Order By: Relevance
“…There was, however, a trend of higher proportions of cannabis use within the last 30 In the total sample, alcohol was the substance most frequently used during the last 30 days prior to admission (80.6%), followed by cannabinoids (44.0%), opioids (25.6%), cocaine (23.3%), benzodiazepines (21.7%), and stimulants (19.3%), as well as others (MDMA (13.0%), hallucinogens (9.4%), GHB (6.3%)). About 35% of the patients (35.8%) reported the use of more than one substance during the last 30 days.…”
Section: Sociodemographic and Substance Use Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…There was, however, a trend of higher proportions of cannabis use within the last 30 In the total sample, alcohol was the substance most frequently used during the last 30 days prior to admission (80.6%), followed by cannabinoids (44.0%), opioids (25.6%), cocaine (23.3%), benzodiazepines (21.7%), and stimulants (19.3%), as well as others (MDMA (13.0%), hallucinogens (9.4%), GHB (6.3%)). About 35% of the patients (35.8%) reported the use of more than one substance during the last 30 days.…”
Section: Sociodemographic and Substance Use Characteristicsmentioning
confidence: 98%
“…In addition, patients had to meet DSM-IV criteria B, C, or D, as well as criteria E and F [28,29]. Criterion A2 was not included into the screening criteria for subsyndromal PTSD because empirical studies have shown that the self-report of A2 is not necessary for PTSD diagnosis [30,31]. The resulting groups were termed "PTSD" (patients with positive screening for PTSD), "subsyndromal PTSD" (patients with positive screening for subsyndromal PTSD), and "SUD-only" (patients with neither PTSD, nor subsyndromal PTSD).…”
Section: Group Allocationmentioning
confidence: 99%
“…To evaluate the presence of PTSD in MS we followed the proposal of previous studies (Chalfant et al, 2004;Hathaway et al, 2010;Dell'Osso and Carmassi, 2001): the Criterion A2 (subjective experience) was modified by asking participants if they felt intense fear or helplessness due to the presence of MS. It is crucial to note that our request was aimed at investigating whether during the last month the patients felt intense fear or helplessness due to the presence of MS, not just thatwhether they were scared or worried about it in the past..…”
Section: Procedurementioning
confidence: 99%
“…Older conceptualisation of a traumatic event (APA, 1994) required the individual to have experienced fear, helplessness or horror at the time of one's exposure to an event involving actual or threatened serious injury, in order to qualify as having been exposed to a traumatic event. Yet this peri-traumatic emotional configuration of fear, helplessness or horror has been removed from current conceptualisations of a traumatic event because of mounting evidence that posttraumatic symptoms could also develop if a person had experienced alternative peritraumatic emotions or even emotional numbing whilst in the process of witnessing or learning about such an event (Bovin & Marx, 2001;Friedman, 2013;Hathaway, Boals, & Banks, 2011). Moreover, in the most recent conceptualisation of post-traumatic stress offered by the DSM-5, a new symptom category was created to exclusively address negative alterations in mood and cognition.…”
Section: Introductionmentioning
confidence: 99%